Correction: Review: a comprehensive summary of a decade development of the recombinase polymerase amplification. Issue 5 (23rd January 2020) - Li, Jia; Macdonald, Joanne; von Stetten, Felix
Abstract : Correction for 'Review: a comprehensive summary of a decade development of the recombinase polymerase amplification' by Jia Li et al., Analyst, 2019, 144, 31–67.